Analisis Faktor-Faktor Pembentuk Kemiskinan Pulau Jawa Periode 2013-2021 - Dhea Cahya Nilam Triana Dewi (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2022)
This study aims to analyze the effect of government spending on the education sector, government spending on health, the Gini index and the regional minimum wage both simultaneously and partially in Java during the period 2013- 2021. This study uses secondary data in the form of time series data with the period 2013-2021 in 6 provinces on the island of Java. The analytical method used is panel data with the chosen estimation model is the Fixed Effect Model (FEM). The results showed that the variables of government expenditure in the education sector and government expenditure in the health sector had a significant effect on poverty, while the Gini index and the regional minimum wage had no effect on poverty in Java during the period 2013- 2021.